Randomized field trial on the effects of body weight and short transport on stress and immune variables in 2‐ to 4‐week‐old dairy calves. (25th March 2019) - Masmeijer, Christien; Devriendt, Bert; Rogge, Tina; van Leenen, Katharina; De Cremer, Lieze; Van Ranst, Bonny; Deprez, Piet; Cox, Eric; Pardon, Bart
Abstract: Background: Whether underweight calves respond differently to transport stress, enhancing their disease risk, is currently unknown. Objective: To determine the effects of low body weight and transport stress on immune variables. Animals: Twenty‐one 2‐ to 4‐week‐old male Holstein calves, housed on a commercial farm. Methods: Randomized clinical trial. Full factorial design with 4 treatment groups: low body weight (≤46 kg)/no transport (LOWCON); low body weight/transport (LOWTRANS); normal body weight (>46 kg)/no transport (NORMCON), and normal body weight/transport (NORMTRANS). Transport duration was 2 hours. Results: Transport significantly increased serum cortisol concentration (77.8 μg/mL; 95% confidence interval [CI], 37.8‐131.6; P < .001), interleukin (IL)‐17A (344.9 pg/mL; 95% CI, 32.2‐556.5; P = .04), and tumor necrosis factor‐α (TNF‐α) (218.2 pg/mL; 95% CI, 32.5‐368.3; P = .03) production after lipopolysaccharide (LPS) stimulation. Body weight did not affect any of the studied variables. However, the interaction of transport and body weight was significant. LOWTRANS calves showed increased monocyte count (2.0 × 10 9 /L; 95% CI, 0.6‐4.2; P < .05) and interleukin IL‐17A production (106.0 pg/mL; 95% CI, 4.2‐306.9; P = .03) compared to normal weight calves and increased TNF‐α production (275.6 pg/mL; 95% CI, 2.6‐463.0; P = .02) compared to LOWCON calves in unstimulated peripheral blood mononuclear cells (PBMCs) after transport. Conclusion and Clinical Importance: These findings contribute to our understanding of increased disease susceptibility of underweight calves when transported. Gamma globulin concentration was identified as important interfering factor in studies on immune variables in neonatal calves.